Fielding before and after baseball's great transformation - Kahan, D. M. (Journal of Sports Analytics, 2025)
This article presents evidence of a dramatic decrease in the importance of differences in team fielding quality in major league baseball. Over the course of the last three decades, the share of variance in runs allowed that is explained by fielding has steadily declined as the share accounted for by fielding-independent pitching has steadily risen. The paper uses a variety of non-digital and digital fielding metrics, including MLB's Statcast, to chart this trend. It also illustrates the practical effect of it on season-long outcomes and on the evaluation of individual player WAR.